2014
DOI: 10.5114/kitp.2014.41929
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy is a risk factor for bronchopleural fistula after pneumonectomy for non-small cell lung cancer

Abstract: IntroductionPerforming pneumonectomy after neoadjuvant chemotherapy is still controversial. Bronchopleural fistula is a major complication after pneumonectomy. In this study the effect of neoadjuvant chemotherapy on postpneumonectomy bronchopleural fistula was investigated.Material and methodsA retrospective review of patients who underwent pneumonectomy for non-small cell lung cancer from January 2005 to December 2011 was undertaken. The major complications and operative mortality were analyzed and compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…However, the pooled OR for NC group appeared an obvious trend towards the increased risk of BPF (OR: 1.857; 95%CI: 0.881-3.911; P = 0.104). Two studies with nearly 1000 surgical patients also demonstrated the significant relationship between NC and occurrence of BPF (42,45). Therefore, the actual effects of NC on risk of BPF need further affirmations and modifications in the future studies based on a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the pooled OR for NC group appeared an obvious trend towards the increased risk of BPF (OR: 1.857; 95%CI: 0.881-3.911; P = 0.104). Two studies with nearly 1000 surgical patients also demonstrated the significant relationship between NC and occurrence of BPF (42,45). Therefore, the actual effects of NC on risk of BPF need further affirmations and modifications in the future studies based on a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…3B). The summarized outcomes integrating 12 available studies (21,26,34,35,37,38,42,(44)(45)(46)(47)50) revealed the higher frequency of BPF occurred in patients treated with NC compared with those without NC (OR: 1.857; 95%CI: 0.881-3.911). However, the current evidences did not show the significant impact of NC on BPF occurrence after lung cancer surgery (P = 0.104).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 3 more Smart Citations